Probability and Statistics for Physical Sciences - Martin, Brian R; Hurwitz, Mark F (London : Elsevier, 2024)
Probability and Statistics for Physical Sciences, Second Edition is an accessible guide to commonly used concepts and methods in statistical analysis used in the physical sciences. This brief yet systematic introduction explains the origin of key techniques, providing mathematical background and useful formulas. The text does not assume any background in statistics and is appropriate for a wide-variety of readers, from first-year undergraduate students to working scientists across many disciplines.Provides a collection of useful formulas with mathematical backgroundIncludes worked examples throughout and end-of-chapter problems for practice.Offers a logical progression through topics and methods in statistics and probability.
Includes appendix, bibliography and index.
Keywords: Probability; Sampling; Hypothesis testing; Estimation